(untitled) (Scientific journal of the Fergana State University, 2024)
Dehydrofluorination of available HFIBA derivatives at first sight seems to be the most convenient way of preparing PFMA derivatives. Yet, the so far reported attempts to carry out this reaction failed to give good results. Thermal dehydrofluorination of methyl ester over NAF yielded a mixture of PFMA ester and the starting saturated ester, which is difficult to separate.